Aging characteristics of neat and modified asphalt binders based on rheological evaluations at intermediate temperatures. (7th March 2022) - Farrokhzade, Farhad; Sabouri, Mohammadreza; Tabatabaee, Nader
Highlights: The base binder and its modified states using CR and SBS were studied. Rheological properties of the binders at their intermediate temperatures were investigated. A new aging/cracking rheological parameter was introduced. Aging indices showed noticeably different aging susceptibilities for the binders. A composite aging index was proposed using four viscoelastic parameters. Abstract: This study examined the aging of neat and modified binders at intermediate temperatures. The neat binder was modified using two crumb rubber (CR) and styrene–butadiene–styrene (SBS) contents. The linear and non-linear rheological test results and parameters exhibited different aging susceptibilities for each binder. A new aging/cracking parameter is introduced based on the Christen-Anderson model. The limiting values are defined to assess cracking potential after PAV aging. The SBS binders were highly sensitive to aging, but the addition of sulfur noticeably improved their rheological and cracking properties and aging resistance. Among the studied parameters, four were deemed suitable to assess the aging of asphalt binders at intermediate temperatures in a comprehensive manner.